2022
DOI: 10.1038/s41587-021-01126-9
|View full text |Cite
|
Sign up to set email alerts
|

Conformation-locking antibodies for the discovery and characterization of KRAS inhibitors

Abstract: The discovery of covalent inhibitors binding the switch II (SWII) pocket has enabled therapeutic intervention in KRAS G12C driven tumors and represents a milestone in targeting KRAS-driven cancers. However, the transient nature and high energetic barrier required for binding this pocket has been an obstacle in successfully targeting other KRAS mutant oncoproteins. We report the discovery of KRAS Conformation Locking Antibodies for Molecular Probe discovery (CLAMP)s that specifically recognize the unique confor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Remarkably, this RAS-specific Nb further inhibits the intrinsic nucleotide exchange of RAS, locking it in a fully inactive conformation. We hypothesize that the interactions of Nb84 with the switch-1 loop of RAS prevent the conformational changes required to exchange the nucleotide, very similar to the conformation-locking antibodies discovered by the Evangelista lab 15 .…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…Remarkably, this RAS-specific Nb further inhibits the intrinsic nucleotide exchange of RAS, locking it in a fully inactive conformation. We hypothesize that the interactions of Nb84 with the switch-1 loop of RAS prevent the conformational changes required to exchange the nucleotide, very similar to the conformation-locking antibodies discovered by the Evangelista lab 15 .…”
Section: Resultsmentioning
confidence: 60%
“…PPI-stabilizing Nanobodies to facilitate precision drug discovery. Because many Nbs act as structural chaperones that stabilize specific conformations or interactions, they facilitate small molecule/fragment library screenings by enhancing the binding of (weak) ligands that bind the same conformer 15,25,26 . Previously, a series of indolo-4-aminopiperidines was previously identified as compounds that binds the SOS1•RAS interface and elicits the acceleration of SOS1-catalyzed nucleotide exchange 8 .…”
Section: Nb14 and Ras•gtp Modulate Sos1 Activity By A Similar Alloste...mentioning
confidence: 99%
“…Together, these data suggested that it would be feasible to design a covalent KRAS G12C inhibitor from the non-covalent binders discovered in this study. In contrast, a previously described fragment (GNE-2897, 13 ) and also the switch II pocket binding core groups of two reported KRAS G12C inhibitors ( 14 , 15 ) did not display tight binding to KRAS without their covalent warheads. We hypothesized that the use of a KRAS binding core with native affinity to the protein should enable the discovery of a covalent inhibitor with greater selectivity against other cysteines and therefore lower toxicity as well as a higher second-order rate constant and improved KRAS G12C inhibition, resulting in a stronger antiproliferative effect.…”
Section: Resultsmentioning
confidence: 70%
“…After homogenization of the core needle biopsy, an aliquot of the lysate with 20 μg of total protein was incubated with anti-RAS antibody clone RAS10, which was pre-immobilized to Protein A magnetic beads. RAS10 has been shown to possess comparable affinity to KRAS G12C with or without covalent modification by immunoprecipitation . After on-bead tryptic digestion, the concentrations of both free and GDC-6036-bound KRAS G12C were determined with 4 μg of total protein using an ultra-sensitive targeted 2D-LC–MS/MS technology, which enables up to 100-fold increase in sensitivity compared to the conventional LC–MS/MS method .…”
Section: Resultsmentioning
confidence: 99%
“…RAS10 has been shown to possess comparable affinity to KRAS G12C with or without covalent modification by immunoprecipitation. 13 After on-bead tryptic digestion, the concentrations of both free and GDC-6036bound KRAS G12C were determined with 4 μg of total protein using an ultra-sensitive targeted 2D-LC−MS/MS technology, which enables up to 100-fold increase in sensitivity compared to the conventional LC−MS/MS method. 12 KRAS G12C engagement was calculated as the ratio of GDC-6036-bound KRAS G12C/ (free KRAS G12C + GDC-6036-bound KRAS G12C).…”
Section: Immunoaffinity Enrichment and Targeted 2d-lc− Ms/ms Approach...mentioning
confidence: 99%